Electromagnetic Exposure Dosimetry Study on Two Free Rats at 1.8 GHz via Numerical Simulation - Wang, Xianghui; Xia, Chengjie; Lu, Lu; Qi, Hongxin; Zhang, Jie (Frontiers in Public Health, 2021)
Normally, the impact of electromagnetic exposure on human health is evaluated by animal study. The biological effect caused by electromagnetic exposure on such experimental animals as rats has been proven to be dose-dependent. However, though the dose of radio frequency (RF) electromagnetic exposure described by the specific absorbing rate (SAR) on fixed rats has been relatively well studied utilizing numerical simulations, the dosimetry study of exposure on free rat is insufficient, especially the cases of two or more free rats. Therefore, the present work focuses on the variation of SAR caused by the existence of neighboring free-rat in the same cage. Here, infrared thermography was used to record the activity of the two free rats who lived in the same cage that mounted at the far-field region in the microwave darkroom for a duration of 48 h. Then, using image processing techniques, the relative positions and orientations of the two rats are identified, which are defined by three parameters including the relative distance (d), relative direction angle (), and relative orientation angle (). Using the simulation software XFdtd 7.3, the influence of d,  and  on the whole-body average SAR (WB-avgSAR) of the rats exposed to 1.8 GHz electromagnetic wave were calculated and analyzed. Then, the average variation of WB-avgSAR of the two rats compared with that of a single rat within 48 h was calculated. The numerical simulation results showed that: the relative posture position described by (d, , ) of the two rats affects their WB-avgSAR and leads to fluctuations at different positions. However, the variation rate of the 48-hour-average WB-avgSAR was only 10.3%, which implied that the over-time average SAR of two or more rats can be roughly described by the WB-avgSAR of a single free rat, except when a real-time precise control of exposure dose is necessary.